Necrotic pancreatitis: modern approaches to the prevention of infected necrosis - Jakanov, Murat K.; Gainollina, Gulnur G.; Zhakiev, Bazylbek S.; Topchiev, Mikhail A.; Kurmanbayev, Bulat A. (Frontiers in Medicine, 2026)
The investigation of etiological factors in acute pancreatitis is a critical task, as their elucidation contributes to advancing both the diagnosis and prevention of the disease. Necrotizing pancreatitis (NP) is a severe complication of acute pancreatitis associated with high morbidity and mortality due to enzymatic tissue destruction, systemic inflammation, and the risk of infected necrosis. This review synthesizes current knowledge on the pathogenesis, classification, and epidemiology of NP, with emphasis on strategies aimed at preventing infectious complications. Evidence consistently supports the protective role of early enteral nutrition, while the use of selective digestive decontamination and antibiotic prophylaxis remains debated. Although several clinical trials and meta-analyses have explored antibiotic prophylaxis, results are inconclusive, reflecting heterogeneity in study design, antibiotic regimens, and patient selection. Recent advances in risk stratification, including the application of machine learning models, offer promising tools for identifying patients at highest risk for infection and tailoring preventive interventions. Nevertheless, important knowledge gaps remain, particularly regarding the optimal timing, duration, and selection of prophylactic measures. Current data suggest that prevention strategies should integrate nutritional support, judicious antimicrobial use, and individualized risk prediction. In conclusion, while significant progress has been made in understanding NP and developing preventive approaches, the efficacy of antibiotic prophylaxis continues to be controversial. Future large-scale, methodologically rigorous studies are needed to establish standardized preventive protocols and ultimately improve clinical outcomes in patients with necrotizing pancreatitis.